Bread, peace and the attrition of power: Economic events and German election results - Irem Batool; Gernot Sieg (Technische Universität Braunschweig, Institut für Volkswirtschaftslehre, 2009)
Aggregate votes for incumbent parties in post-war Germany were determined by the weighted-average growth of real per capita disposable income. Each percentage point of per capita real disposable income growth sustained over the legislative term yielded approximately two percentage points of votes in Germany. No other economic variables add value or significantly perturb the coefficients of our model. However, attrition of power reduced the vote share in election years 1961, 1994 and 1998.
urn:nbn:de:gbv:084-24452
Keywords: E6; H11; P16; 330; bread and peace model; elections; vote share; real per capita disposable income growth